Price Analysis and Brand Identity on Customer Loyalty through Customer Satisfaction Mediation - Arbiya Magfiroh Rohmi; Sriyono Sriyono; Wisnu Panggah Setiyono (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research aims to find out whether customer satisfaction mediates the relationship between price and brand identity on consumer loyalty. The sampling technique in this research used the accidental sampling method by distributing questionnaires to 150 respondents. The data analysis method was carried out using several statistical tests: research instrument testing (validity and reliability testing) and hypothesis testing. The research results show that: (1) brand identity has a positive influence on customer satisfaction. (2) brand identity has a positive influence on consumer loyalty. (3) Price has a positive influence on customer satisfaction. (4) price has a positive influence on consumer loyalty. (5) brand identity through customer satisfaction influences consumer loyalty. (6), price through customer satisfaction has a significant effect on consumer loyalty.